A conciliação família e teletrabalho na pandemia da Covid-19: (re)pensando vivências de mulheres educadoras infantis - Andrade, Cristiano de Jesus (2022)
The world finds itself in a pandemic crisis of intensity and scales not seen since the last century. Both the risks related to the infection and the need for social distancing have impacted the lives of all and, particularly, of the families where mothers of young children are found. Since women have had their routines altered by the need to move away from the professional and personal support network, but they still need to continue reconciling family and career. Having as a problem of research, family and professional activity present themselves to teleworkers women in early childhood education in a conflicting way or as processes and experiences that can be reconciled? The aim of this study was to analyze the implications that the exercise of telework in the context of early childhood education, generates in the subjectivity of women in conciliation with the care inherent to the family. This is a qualitative, descriptive research with cross-sectional approach. The sample consisted of 30 women/mothers of children aged between 02 and 17 years and 11 months, who developed activities as teleworkers in the area of early childhood education in the pandemic time of Covid-19. They are employed workers, concursadas of the city of Poços de Caldas / MG, where they also reside. For this, the instrument used was the semi-structured interview to identify the subjective experiences in the participants' family and work routines. This was sent by e-mail before it was even applied, because it was desired that they would accompany what they intended to question. All interviews were conducted remotely, because the period of data collection was at the stage in which covid-19 contagion numbers were high. Thus, thinking about protecting the participants, as well as the researcher, all agreed to chat through the Microsoft Teams application. As results, it was identified that telework in the context of early childhood education, although it was necessary to fulfill the social distancing proposed as a measure of containment of the virus. For these women, it acted as a complicator in their routines. Since it made their attributions even more, leading them to experience high levels of collections, which resulted in psychic suffering in their journeys. Understanding that the bond with the family was maintained, but the relationships in general with it were compromised, since the lack of time operated as a limiting factor of personal experiences. It is expected that the findings will contribute to health professionals developing intervention strategies for the prevention of mental suffering, health promotion and identification of protective factors and psychological and social risk factors in this population.(AU)